Clinical impact in the real life of guidelines recommendations for atopic dermatitis in a tropical population (TECCEMA cohort) (2017)
ABSTRACT: Background: Real-life impact of guidelines for the management of atopic dermatitis has been poorly studied. Objective: To assess atopic dermatitis clinical control in residents of a tropical area managed according to international consensuses. Methods: Prospective study with a 24-month follow-up. Clinical response was assessed with SCORAD, DLQI and a subjective scale (SS) on severity perception by the patient. Results: Two-hundred and thirty-three patients were stratified according to SCORAD: 53 had mild severity (22%), 116 moderate (49%) and 64 severe (27%). Baseline SCORAD mean was 33 (15-41), for DLQI, it was 14 (11-20), and for the subjective scale, 85% (67-99). At 6 months, there was significant reduction (p < 0.5): SCORAD 29 (14-41), DLQI 12 (8-16) and subjective scale 62% (45-80). At 2 years, SCORAD was 21 (9-34), DLQI 7 (4-10) and subjective scale 41% (27-56); only 33% achieved complete control (SCORAD < 15%, DLQI < 5, subjective scale < 20%). Conclusions: Following international guidelines’ recommendations reduces eczema severity and improves quality of life, although only 33% achieved complete control after 2 years.